2000
DOI: 10.1086/321196
|View full text |Cite
|
Sign up to set email alerts
|

Identification ofMEFV‐Independent Modifying Genetic Factors for Familial Mediterranean Fever

Abstract: Familial Mediterranean fever (FMF) is a recessively inherited disorder predisposing to renal amyloidosis and associated with mutations in MEFV, a gene encoding a protein of unknown function. Differences in clinical expression have been attributed to MEFV-allelic heterogeneity, with the M694V/M694V genotype associated with a high prevalence of renal amyloidosis. However, the variable risk for patients with identical MEFV mutations to develop this severe complication, prevented by lifelong administration of colc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 33 publications
2
23
0
Order By: Relevance
“…It is clear that the genotypes at the SAA1 locus are associated with a susceptibility to develop AA- amyloidosis, although it appears that the susceptible alleles differ amongst different ethnic populations [9][10][11][12][13][14][15][16][17]. So far, there has been no reported study indicating the mechanism whereby the allelic variants at the SAA1 locus influence amyloidogenicity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is clear that the genotypes at the SAA1 locus are associated with a susceptibility to develop AA- amyloidosis, although it appears that the susceptible alleles differ amongst different ethnic populations [9][10][11][12][13][14][15][16][17]. So far, there has been no reported study indicating the mechanism whereby the allelic variants at the SAA1 locus influence amyloidogenicity.…”
Section: Discussionmentioning
confidence: 99%
“…While an MEFV missense mutation, M694V, is associated with a severe course of FMF and developing AA-amyloidosis [2][3][4][5][6][7][8], the risk associated with the SAA1 gene and developing AAamyloidosis is still controversial. Although homozygosity for SAA1.1 is reported to be a risk factor for the development of AA-amyloidosis in patients with FMF [9][10][11] and in Caucasians with RA [12,13], this is not the case in the Japanese RA population. The SAA1.3 allele and not the SAA1.1 allele was closely associated with AA-amyloidosis in Japanese RA patients [14][15][16][17], with the SAA1.1 allele frequency being significantly less in Japanese AA-amyloidosis patients than in controls.…”
Section: Introductionmentioning
confidence: 94%
“…But no relation between SAA1 and amyloidosis could be demonstrated. Cazeneuve et al [16] reported a 7-fold increased risk for amyloidosis in the SAA1 α/α genotype by detecting the relation between the SAA1 and SAA2 genotypes in FMF patients. Yılmaz et al [18] evaluated the SAA and TNFα gene polymorphisms in 173 Turkish patients with amyloidosis.…”
Section: Discussionmentioning
confidence: 99%
“…Catabolism of overproduced SAA protein is disturbed and it is deposited in the form of protease-resistant fibrils mainly in phagocytic cells in tissues. In SAA1 gene polymorphism especially the SAA1 α/α genotype has been found to facilitate the development of amyloidosis in FMF patients [16,17,18,19,20]. …”
Section: Introductionmentioning
confidence: 99%
“…This, despite of increased awareness, and the availability of DNA testing. In recent years several studies indicate that genotypephenotype relationships for FMF are unpredictable [42,43].…”
Section: Familial Mediterranean Fevermentioning
confidence: 99%